Art and conservation - Dent, Hugh R (Rhodes University, Faculty of Humanities, Department of Fine Art, 1975)
There can be no doubt that population increase and environmental pollution are the world's biggest problems today. These pose serious threats to the quality of life and art. They can only be remedied by an efficient system of birth-control and sound compulsory education, in order to regain spiritual enlightenment. Intro. p. 1.
Keywords: Nature conservation; Environmentalism; Nature (Aesthetics)